Analisis Efisiensi Produksi Dan Pendapatan Usaha Tani Ubi Kayu (Manihot Utilissima) - Antonius Marthen Nggaba (BiSTeK Pertanian, 2022)
Cassava crops (Manihot utilissima) are well known and widely cultivated by rural and suburban communities, adaptable to the environment or marginal and dry climates, the risk of small crop failure and drought tolerance. Based on the above, it is necessary to study the efficiency of production and income of farmers in cassava farming. The objective is to know the factors of production that influence the production of cassava, the efficiency of the use of cassava production factor and the profit of farmers in the cassava farming. Population in this research is member of farmer group Budi Makmur which amounts to 25 people in in one farmer group, Location of Dusun SumberTempur Kidul SumberTempur Village Wonosari District, Malang Regency